Inbreeding versus Crossbreeding: the Potential Bias of Breeding Values in Dutch Dairy Cattle - Snelder, Jikke (Student Undergraduate Research E-journal!, 2019)
Inbreeding and crossbreeding oppositely affect the performance of livestock; inbreeding negatively- and crossbreeding positively affects all traits. This study examined if it is appropriate that breeding value estimations (EBVs) in Dutch dairy cattle only take into account the effects of crossbreeding (heterosis). Performance and EBVs for milk yield, fat, and protein; somatic cell count; and fertility of 219 purebred Holstein Friesian cows and 191 crossbred cows were compared. The outcomes suggest a bias in the EBVs for milk yield, and fat; and fertility, that may very well be caused by inbreeding depression.